Hip Dysplasia and Dislocation in Down Syndrome: Is There Evidence to Support Consideration of Routine Hip Surveillance? - Rikki Koehler, MD; Rubini Pathy, MD; Daniel Gregory, PhD; James F. Mooney, III, MD; Mary E. Gannotti, PT, PhD (Journal of the Pediatric Orthopaedic Society of North America)
ABSTRACT: Background: Hip instability is associated with Down syndrome (DS). The goal of this review was to examine the existing literature to determine whether there is sufficient evidence to consider the development of standardized hip surveillance guidelines in patients with DS. Methods: A scoping review following Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines identified English-language, peer-reviewed publications concerning hip instability or dysplasia in people with DS, including diagnosis and imaging, physical examination, other hip pathologies, surgical and nonsurgical interventions, and epidemiology from gestation to adulthood. PubMed/MEDLINE, EMBASE, Web of Science, and Cochrane databases were queried with professional librarian assistance. Two independent reviewers screened abstracts and full texts. Discrepancies were resolved by group consensus. Validated critical appraisal tools were used. Results: Eight hundred seventy-six articles were screened, and 54 full-text articles with case series, cross-sectional, and case-control designs met the criteria. Twenty-six articles have described pelvic morphology in people with DS including increased iliac indices, acetabular retroversion, and global acetabular insufficiency compared to peers. Studies have shown that 1.0% to 14% of pediatric DS patients and up to 28% of adults with DS have evidence of radiographic hip abnormality. Conclusions: A scoping review of the literature demonstrates that the risk of hip pathology among children and adults with DS is increased independent of life stage. Consideration of early and regular radiographic and physical examination of DS patients focused on potential hip pathology, may be warranted. Key Concepts: (1) There is evidence of a significant risk of hip pathology in patients with Down syndrome. (2) To date, a focused review of the existing literature has been limited. (3) A scoping review demonstrates that regular and routine hip surveillance in patients with Down syndrome may be indicated. Level of Evidence: V